Development of passenger transportation by railroad from Lithuania to European States - Butkevičius, Jonas (Transport, 2007)
With the entry of Lithuania into the European Union, proper conditions for both Lithuanian and the EU inhabitants to comfortably travel by trains should be created. Lithuania should resume the direct communication by railroads with Poland. For that the passenger train route “Vilnius‐Warsaw” should be opened; it would enable the national inhabitants to reach European countries by train and also the inhabitants of those countries to come by train to Lithuania. The article gives an analysis of perspective passenger flows on the route “Vilnius‐Warsaw”, presents results of the study on passenger transportation of competitive sphere on this route, investigates technical‐economical aspects of the train’s launch, analyses the marketing strategy, gives a survey of links of this train’s launch with the “Rail Baltica” project, provides with a presentation of the SWOT analysis. The author proposes to include St. Petersburg into the “Rail Baltica” route ‐ this would increase flows of both – passengers and cargoes. The article covers redistribution of the international passenger transportation market among different types of transport following the introduction of the “Rail Baltica” route. First Published Online: 27 Oct 2010